Global Latin America : into the twenty-first century - Gutmann, Matthew C., 1953-; Lesser, Jeff (Global square ;, 2016)
"Latin America has a unique historical and cultural context, is home to emerging global powers such as Brazil and Mexico, and is tied to world regions including China, India, and Africa. Global Latin America considers this regional interconnectedness and examines its meaning and impact in a global world. Its innovative essays, interviews, and stories highlight the insights of public intellectuals, political leaders, artists, academics, and activists, thereby allowing students to gain an appreciation of the diversity and global relevance of Latin America in the twenty-first century"--Provided by publisher